P = n = 1 ∑ ∞ n ( − 1 ) n , Q = n = 0 ∑ ∞ n ! n 3
For P and Q as defined above, find the value of ( 5 Q ) 5 P .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just amazing!
The first one ( P ), just google it up under "alternating sum of reciprocals".
For the second one ( Q ), in language of exponential generating function, defining Q ( x ) = ∑ n = 0 ∞ n ! n 3 x n , you need to calculate Q ( 1 ) . Knowing e x = ∑ n = 0 ∞ n ! 1 x n , Q ( x ) = D 3 ⋅ e x , where operator D , that acts on a function of x , is basically taking derivative and multiplying the result by x . There rest is easy!
We are going to use some Taylor expansions here, but before let's take a quick recap.
F ( x ) = n = 0 ∑ ∞ n ! [ F ( n ) ( a ) ] ( x − a ) n
Where x is variable, a is constant and F ( n ) ( x − a ) means the n t h derivative of the Function.
Now keeping F ( x ) = e x [ e is the Euler's number ] and a = 0 , we get the Taylor expansion as :
e x = 0 ! x 0 + 1 ! x 1 + 2 ! x 2 + . . .
Thus , e x = ∑ n = 0 ∞ n ! x n
From this we can say that n = 0 ∑ ∞ n ! 1 n = e 1 = e
∑ n = 0 ∞ n ! n
= 0 ! 0 + ∑ n = 1 ∞ n ! n = ∑ n = 1 ∞ ( n − 1 ) ! 1
= ∑ n = 0 ∞ n ! 1 = e
∑ n = 0 ∞ n ! n ²
= 0 ! 0 + ∑ n = 1 ∞ n ! n ² = ∑ n = 1 ∞ ( n − 1 ) ! n
= ∑ n = 0 ∞ n ! n + 1
= ∑ n = 0 ∞ n ! n + ∑ n = 0 ∞ n ! 1 = e + e
= 2 e
∑ n = 0 ∞ n ! n ³
= 0 ! 0 + ∑ n = 1 ∞ n ! n ³ = ∑ n = 1 ∞ ( n − 1 ) ! n ²
= ∑ n = 0 ∞ n ! ( n + 1 ) ²
= ∑ n = 0 ∞ n ! n ² + 2 n + 1
= ( 2 e ) + 2 ( e ) + 1 ( e ) = 5 e
Thus Q = 5 e
Next if we take F ( x ) = L n ( 1 + x ) [ Ln is the Natural Logarithm ] , − 1 ≤ x ≤ 1 and a = 0 , we get the Taylor expansion as :
L n ( 1 + x ) = 1 x − 2 x ² + 3 x ³ − 4 x ⁴ + . . .
So , L n ( 1 + x ) = ∑ n = 1 ∞ n − ( x n ) ( − 1 ) n
If we keep x = 1 here , then we get the following result :
L n ( 1 + 1 ) = ∑ n = 1 ∞ n − ( 1 n ) ( − 1 ) n
L n ( 2 ) = ∑ n = 1 ∞ n − ( − 1 ) n
Or we can say P = − L n ( 2 )
Now we need to find the value of ( Q / 5 ) ( 5 P )
= ( ( 5 e ) / 5 ) ( 5 ( − L n 2 ) )
= ( e ) ( L n ( 2 − 5 ) )
= 2 − 5 = 3 2 1
= 0 . 0 3 1 2 5
Problem Loading...
Note Loading...
Set Loading...
We note that the Maclaurin series of
ln ( 1 + x ) n = 1 ∑ ∞ n ( − 1 ) n ⟹ P = x − 2 x 2 + 3 x 3 − ⋯ = n = 1 ∑ ∞ n ( − 1 ) n + 1 x n = − n = 1 ∑ ∞ n ( − 1 ) n + 1 x n ∣ ∣ ∣ ∣ x = 1 = − ln ( 1 + 1 ) = − ln 2 = − ln 2
Using Maclaurin series again,
n = 0 ∑ ∞ n ! x n n = 0 ∑ ∞ n ! n x n − 1 n = 0 ∑ ∞ n ! n x n n = 0 ∑ ∞ n ! n 2 x n − 1 n = 0 ∑ ∞ n ! n 2 x n n = 0 ∑ ∞ n ! n 3 x n − 1 n = 0 ∑ ∞ n ! n 3 x n n = 0 ∑ ∞ n ! n 3 ⟹ Q = e x = e x = x e x = e x + x e x = x e x + x 2 e x = e x + x e x + 2 x e x + x 2 e x = x e x + 3 x 2 e x + x 3 e x = 5 e = 5 e Differentiate both sides w.r.t. x Multiply both sides by x Differentiate both sides w.r.t. x Multiply both sides by x Differentiate both sides w.r.t. x Multiply both sides by x Putting x = 1
Therefore, ( 5 Q ) 5 P = e − 5 ln 2 = 3 2 1 = 0 . 0 3 1 2 5 .